Neutron and synchrotron probes in the development of Co–Re‐based alloys for next generation gas turbines with an emphasis on the influence of boron additives. (1st August 2014) - Mukherji, D.; Gilles, R.; Karge, L.; Strunz, P.; Beran, P.; Eckerlebe, H.; Stark, A.; Szentmiklosi, L.; Mácsik, Z.; Schumacher, G.; Zizak, I.; Hofmann, M.; et al.
<x xml:space="preserve">Abstract</x> Nickel‐based superalloys are the materials of choice in the hot section of current gas turbines, but they are reaching temperature limits constrained by their melting temperature range. Co–Re alloy development was prompted by a search for new materials for future gas turbines, where the temperature of application will be considerably higher. Addition of the very high melting point refractory metal Re to Co can increase the melting range of Co alloys to much higher temperatures than the commercial Co alloys in use today. The alloy development strategy is first discussed very briefly. In this program, model ternary and quaternary compositions were studied in order to develop a basic understanding of the alloy system. In situ neutron and synchrotron measurements (small and wide angle) at high temperatures were extensively used for this purpose and some selected results from the in situ measurements are presented. In particular, the effect of boron doping in Co–Re–Cr alloys and the stability of the TaC precipitates at high temperatures were investigated. A fine dispersion of TaC precipitates strengthens some Co–Re alloys, and their stability at the application temperature is critical for the long‐term creep properties.